Respuesta :
1 + 1.5x - 3 is one possibility. That's what you get when you remove the brackets.
There are no expressions to choose from, but if you're simplifying, it would look like this:
=1/2(2+3x−6)
multiply 1/2 by all in parentheses
=(1/2*2)+(1/2*3x) + (1/2*-6)
=2/2 + 3/2x - 6/2
=1 + 3/2x - 3
combine like terms
=3/2x - 2 improper fraction
OR
=1 1/2x - 2 mixed fraction
ANSWER: 3/2x-2 or 1 1/2x-2
Hope this helps! :)
=1/2(2+3x−6)
multiply 1/2 by all in parentheses
=(1/2*2)+(1/2*3x) + (1/2*-6)
=2/2 + 3/2x - 6/2
=1 + 3/2x - 3
combine like terms
=3/2x - 2 improper fraction
OR
=1 1/2x - 2 mixed fraction
ANSWER: 3/2x-2 or 1 1/2x-2
Hope this helps! :)